2007
DOI: 10.1111/j.1442-9993.2007.01698.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape ecology of the burrowing bettong: Warren distribution and patch dynamics in semiarid eastern Australia

Abstract: In arid and semiarid Australia fossorial vertebrates have been a major component of the soil biota mediating many fundamental landscape processes. However, many species such as the burrowing bettong (Bettongia lesueur) have become seriously depleted following European pastoral settlement. As 'landscape engineers', they were responsible for creating and maintaining a high degree of surface heterogeneity that promoted a diverse and productive herbaceous understorey, particularly in 'hard-red' communities dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
5
41
0
Order By: Relevance
“…While biocide treatment at ''Glenora'' initially appeared to induce some slaking of the surface soil in the woollybutt plots, no significant differences in either bulk density or water infiltration were recorded. Bulk density values were similar to those recorded in another study on ''Glenora'' in soils adjacent to warrens constructed by the burrowing bettong (Bettongia lesueur) (Noble et al, 2007). The lack of any significant soil physical differences between biocide and control treatments may indicate that the effectiveness of the biocide had been significantly diminished simply through leaching by rainfall in the intervening period of 10 years between biocide application and soil sampling.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While biocide treatment at ''Glenora'' initially appeared to induce some slaking of the surface soil in the woollybutt plots, no significant differences in either bulk density or water infiltration were recorded. Bulk density values were similar to those recorded in another study on ''Glenora'' in soils adjacent to warrens constructed by the burrowing bettong (Bettongia lesueur) (Noble et al, 2007). The lack of any significant soil physical differences between biocide and control treatments may indicate that the effectiveness of the biocide had been significantly diminished simply through leaching by rainfall in the intervening period of 10 years between biocide application and soil sampling.…”
Section: Discussionsupporting
confidence: 61%
“…Soil biota play a critical role in maintaining soilbased processes in semi-arid landscapes although direct links between such diverse taxa and rates and efficiency of various landscape functions are much less clear (Giller et al, 1997;Jones et al, 1994;Whitford, 2002;Whitford et al, 1992). Even though preliminary studies have shown clear spatial patterning of surface soil features 'engineered' by vertebrates such as the burrowing bettong (Bettongia lesueur) (Noble et al, 2007) and invertebrates such as the harvester termite (Drepanotermes perniger) (Noble et al, 1989), little is known of the relationships between vegetation mosaics and ecosystem processes and their mediation by soil invertebrates in semi-arid ecosystems of Australia.…”
Section: Introductionmentioning
confidence: 97%
“…1). The role of burrowers in profoundly affecting soil, nutrient and vegetation properties in the adjacent landscape has been well documented (Andersen and Kay, 1999;Eldridge et al, 2006;Kinlaw, 1999;Winter et al, 2002) and a recent study by Noble et al (2007) reveals persistent productivity increases associated with burrowing bettong warrens. Our study also suggests that ecosystem services extend to effects on localised invertebrate communities.…”
Section: Invertebratesmentioning
confidence: 97%
“…Their decline has been attributed to persecution by pioneering farmers (Short, 1998) and predation by feral cats, foxes or dingoes (Canis familiaris dingo), which were often exacerbated by plagues of the European rabbit (Oryctolagus cuniculus), pastoralism and altered fire regimes (Corbett, 1995;Smith and Quin, 1996). Bilbies, bettongs and rabbits may occupy burrows or warrens constructed by each other (Arid Recovery, unpublished data; Noble et al, 2007). Bilbies are the most accomplished burrowers of this group and their discarded burrows may be subsequently reworked into large complex warren systems by burrowing bettongs or rabbits, which in turn may be enlarged into dens by cats, foxes and dingoes in some habitats (pers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation